(untitled) (Journal of Computational Mathematics, 1983)
In this paper we establish the Haar and Walsh systems on a triangle. These systems are complete in L_2(Δ). The uniform convergence of the Haar-Fourier series and the uniform convergence by group of the Walsh-Fourier series for any continuous function are proved.